Номинации социологических страт: коннотации и оценка - Ольга Фролова (Studia Rossica Posnaniensia)
The article examines the semantics of social status nominations in the Soviet and post-Soviet periods. The values of nouns of the nobility, peasants, serfs, merchants, courtiers, and intellectuals are analyzed. Using material from the National Russian Corpus, word combinations with these adjectives are considered, which allows us to reveal the connotations of social status. The adjective 'courtier' has formed the meaning 'close to the power and serving its interests', because it is freely combined with the names of professions whose representatives are deprived of an independent position: journalist, sociologist, director.